Regulatory role of RNA N6-methyladenosine modifications during skeletal muscle development - Yu, Baojun; Liu, Jiamin; Zhang, Juan; Mu, Tong; Feng, Xiaofang; Ma, Ruoshuang; Gu, Yaling (Frontiers in Cell and Developmental Biology, 2022)
Functional cells in embryonic myogenesis and postnatal muscle development undergo multiple stages of proliferation and differentiation, which are strict procedural regulation processes. N6-methyladenosine (m6A) is the most abundant RNA modification that regulates gene expression in specific cell types in eukaryotes and regulates various biological activities, such as RNA processing and metabolism. Recent studies have shown that m6A modification-mediated transcriptional and post-transcriptional regulation plays an essential role in myogenesis. This review outlines embryonic and postnatal myogenic differentiation and summarizes the important roles played by functional cells in each developmental period. Furthermore, the key roles of m6A modifications and their regulators in myogenesis were highlighted, and the synergistic regulation of m6A modifications with myogenic transcription factors was emphasized to characterize the cascade of transcriptional and post-transcriptional regulation during myogenesis. This review also discusses the crosstalk between m6A modifications and non-coding RNAs, proposing a novel mechanism for post-transcriptional regulation during skeletal muscle development. In summary, the transcriptional and post-transcriptional regulatory mechanisms mediated by m6A and their regulators may help develop new strategies to maintain muscle homeostasis, which are expected to become targets for animal muscle-specific trait breeding and treatment of muscle metabolic diseases.